Una escriptura dramàtica per als noranta. (Notes de lectura) - Sirera, Josep Lluís (Caplletra. Revista Internacional de Filologia, 2015)
A study of theatrical production from the mid-eighties to the present day. An enquiry into the most relevant thematic and technical approaches, based on the rediscovery of textual proposals as well as the innovative conception of many of the most significant plays.